Surgical Education and Health Care Reform: Defining the Role and Value of Trainees in an Evolving Medical Landscape. Issue 3 (March 2017) - Fayanju, Oluwadamilola M.; Aggarwal, Reena; Baucom, Rebeccah B.; Ferrone, Cristina R.; Massaro, David; Terhune, Kyla P.
Abstract : Objective: Health care reform and surgical education are often separated functionally. However, especially in surgery, where resident trainees often spend twice as much time in residency and fellowship than in undergraduate medical education, one must consider their contributions to health care. Summary Background Data: In this short commentary, we briefly review the status of health care in the United States as well as some of the recent and current changes in graduate medical education that pertain to surgical trainees. Methods: This is a perspective piece that draws on the interests and varied background of the multiinstitutional and international group of authors. Results: The authors propose 3 main areas of focus for research and practice— (1) accurately quantifying the care provided currently by trainees, (2) determining impact to trainees and hospital systems of training parameters, focusing on long-term outcomes rather than short-term outcomes, and (3) determining practice models of education that work best for both health care delivery and trainees. Conclusions: The authors propose that surgical education must align itself with rather than separate itself from overall health care reform measures and even individual hospital financial pressures. This should not be seen as additional burden of service, but rather practical education in training as to the pressures trainees will face as future employees. Rethinking the contributions and training of residents and fellows may also synergistically work to impress to hospital administrators that providing better, more focused and applicable education to residents and fellows may have long-term, strategic, positive impacts on institutions.